2019
DOI: 10.1590/0001-3765201920181330
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol and resveratrol-hydroxypropyl-β-cyclodextrin complex recovered the changes of creatine kinase and Na+, K+-ATPase activities found in the spleen from streptozotocin-induced diabetic rats

Abstract: How to cite: KOOLING J ET AL. 2019. Resveratrol and resveratrol-hydroxypropyl-β-cyclodextrin complex recovered the changes of creatine kinase and Na + , K + -ATPase activities found in the spleen from streptozotocin-induced diabetic rats. An Acad Bras Cienc 91: e20181330.Abstract: Type 1 diabetes (T1D) is the result of the selective destruction of the pancreatic β-cells by T cells of the immune system. Although spleen is a secondary lymphoid organ, it is also involved in the T1d pathogenesis. However, the alte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…Adenylate kinase (AK), CK and PK are key enzymes for balance the homeostasis energy. These systems operate together, when there a decrease in one enzyme the increase activity of the other can be compensated, for this reason is necessary evaluation for the system complete (Kolling et al 2019). The results of our study demonstrated that no changes were found in the PK activity on the groups compared to the control in both organs.…”
Section: Discussionmentioning
confidence: 56%
“…Adenylate kinase (AK), CK and PK are key enzymes for balance the homeostasis energy. These systems operate together, when there a decrease in one enzyme the increase activity of the other can be compensated, for this reason is necessary evaluation for the system complete (Kolling et al 2019). The results of our study demonstrated that no changes were found in the PK activity on the groups compared to the control in both organs.…”
Section: Discussionmentioning
confidence: 56%
“…Resveratrol exerts an antitumour effect by regulating various targets in cancer cells (Ko et al, 2017). Resveratrol can fully recover Na + and K + ‐ATPase activity in spleen tissue from diabetic rats after hyperglycemia has altered the energetic homeostasis of this tissue by reducing enzyme activity levels (Kolling et al, 2019). Because the Na + gradient, maintained actively by Na + , K + ‐ATPase, and/or Na + ‐ATPase enzymes, plays a crucial role in inward Pi flux (Levi et al, 2019; Russo‐Abrahão et al, 2018), the ability of resveratrol to inhibit Na + ‐ATPase or Na + , K + ‐ATPase was investigated, as well as the consequent uptake of sodium‐dependent Pi.…”
Section: Resultsmentioning
confidence: 99%
“…10 As expected, streptozotocin lowered body mass and shrank the spleen while raising blood glucose levels. 11 Reduction in pancreatic weight could perhaps be attributed to the elimination of insulin-producing cells and the subsequent destruction and disappearance of pancreatic islets. 12 The functions of the adrenal glands in biology are diverse and include functions in immunity, inflammation, metabolism, osmoregulatory regulation, and development.…”
Section: Discussionmentioning
confidence: 99%